MINI REVIEW: POTENSI FLORA SULAWESI SELATAN UNTUK SINTESIS NANOPARTIKEL RAMAH LINGKUNGAN - Andi Eka Kartika (JURNAL ATOMIK, 2025)
South Sulawesi harbors a high diversity of plant species, including several endemic taxa with substantial potential for the development of environmentally sustainable nanomaterials. Among emerging approaches, the green synthesis of nanoparticles using plant extracts as bioreducing and capping agents has gained significant attention due to its simplicity, low cost, and alignment with green chemistry principles. This mini-review provides an overview of recent advancements in the biosynthesis of nanoparticles mediated by local and endemic plant species from South Sulawesi. The review highlights the role of phytochemicals in nanoparticle formation, the characterization methods employed, and their potential applications in biomedical, catalytic, and environmental fields. Furthermore, it discusses the current challenges, including standardization of plant extracts, control over nanoparticle morphology, and scalability of the process. The findings emphasize the untapped potential of South Sulawesi flora as a promising biological resource for sustainable nanoparticle synthesis and encourage further interdisciplinary research in this area.